Electronic communication in phosphine substituted bridged dirhenium complexes – clarifying ambiguities raised by the redox non-innocence of the C4H2- and C4-bridges. Issue 13 (3rd March 2016) - Li, Yan; Blacque, Olivier; Fox, Thomas; Luber, Sandra; Polit, Walther; Winter, Rainer F.; Venkatesan, Koushik; Berke, Heinz
Abstract : Dinuclear rhenium complexes with C4 H2 - or C4 - bridges can show open or closed shell structures. Abstract : The mononuclear rhenium carbyne complex trans -[Re(CCSiMe3 )(C–Me)(PMe3 )4 ][PF6 ] (2 ) was prepared in 90% yield by heating a mixture of the dinitrogen complex trans -[ReCl(N2 )(PMe3 )4 ] (1 ), TlPF6, and an excess of HCCSiMe3 .2 could be deprotonated with KO t Bu to the vinylidene complex trans -[Re(CCSiMe3 )(CCH2 )(PMe3 )4 ] (3 ) in 98% yield. Oxidation of3 with 1.2 equiv. of [Cp2 Fe][PF6 ] at −78 °C gave the Cβ –C′β coupled dinuclear rhenium biscarbyne complex trans -[(Me3 SiCC)(PMe3 )4 ReC–CH2 –CH2 –CRe(PMe3 )4 (CCSiMe3 )][PF6 ]2 (5 ) in 92% yield. Deprotonation of5 with an excess of KO t Bu in THF produced the diamagnetic trans -[(Me3 SiCC)(PMe3 )4 ReCCH–CHCRe(PMe3 )4 (CCSiMe3 )] complex ( E -6(S) ) in 87% yield with an E -butadienediylidene bridge. Density functional theory (DFT) calculations of E -6(S) confirmed its singlet ground state. The Z -form of6 ( Z -6(S) ) could not be observed, which is in accord with its DFT calculated 17.8 kJ mol −1 higher energy. Oxidation of E -6 with 2 equiv. of [Cp2 Fe][PF6 ] resulted in the stable diamagnetic dicationic trans -[(Me3 SiCC)(PMe3 )4 ReC–CHCH–CRe(PMe3 )4 (CCSiMe3 )][PF6 ]2 complex ( E -6[PF6 ]2 ) with an ethylenylidene dicarbyne structure of the bridge. The paramagnetic mixed-valence (MV) complex E -6[PF6 ] was obtained by comproportionation of E -6(S) and E -6[PF6 ]2 or by oxidation of E -6(S) with 1 equiv. of [Cp2 Fe][PF6 ]. The dicationic trans -[(Me3 SiCC)(PMe3 )4 ReC–CC–CRe(PMe3 )4 (CCSiMe3 )][PF6 ]2 (7[PF6 ]2 ) complex, attributed a butynedi(triyl) bridge structure, was obtained by deprotonation of E -6[PF6 ]2 with KO t Bu followed by oxidation with 2 equiv. of [Cp2 Fe][PF6 ]. The neutral complex7 could be accessed best by reduction of7[PF6 ]2 with KH in the presence of 18-crown-6. According to DFT calculations7 possesses two equilibrating electronic states: diamagnetic7(S) and triplet7(F) with ferromagnetically coupled spins. The latter is calculated to be 5.2 kcal mol −1 lower in energy than7(S) . There is experimental evidence that7(S) prevails in solution.7 could not be isolated in the crystalline state and is unstable transforming mainly by H-abstraction to give E -6(S) . UV-Vis-NIR spectroscopy for the dinuclear rhenium complexes E -6(S), E -6[PF6 ] and E -6[PF6 ]2, as well as EPR spectroscopic and variable-temperature magnetization measurements for the MV complex E -6[PF6 ] were also conducted. Spectro-electrochemical reduction studies on7[PF6 ]2 allowed the characterization of the mono- and direduced forms of7 + and7 by means of IR- and UV-Vis-NIR-spectroscopy and revealed the chemical fate of the higher reduced form.